Understanding the trilemma of fast charging, energy density and cycle life of lithium-ion batteries - Yang, Xiao-Guang; Wang, Chao-Yang (Journal of power sources, 2018)
Increasing energy density of Li-ion batteries (LiBs) along with fast charging capability are two key approaches to eliminate range anxiety and boost mainstream adoption of electric vehicles (EVs). Either the increase of energy density or of charge rate, however, heightens the risk of lithium plating and thus deteriorates cell life. The trilemma of fast charging, energy density and cycle life are studied systematically in this work utilizing a physics-based aging model with incorporation of both lithium plating and solid-electrolyte-interphase (SEI) growth. The model is able to capture the key feature of temperature-dependent aging behavior of LiBs, or more specifically, the existence of an optimal temperature with the longest cycle life. We demonstrate that this optimal temperature is a result of competition between SEI growth and lithium plating. Further, it is revealed that either the increase of charge rate or of energy density accelerates lithium plating induced aging. As such, the optimal temperature for cell life increases from ∼20 °C for a high-power cell at 1C charge to ∼35–45 °C with the increase of charge rate and/or energy density. It would be beneficial to further increase the charge temperature in order to enable robust fast charging of high energy EV cells. [Display omitted] •Temperature-dependent aging behavior of Li-ion battery is studied numerically.•Overall aging rate depends on the competition of lithium plating and SEI growth.•The optimal temperature for cycle life increases with charge rate & energy density.•Raising charging temperature is an effective method to eliminating lithium plating.